EPID-03. Epidemiology, treatment and outcomes of children and young adults with CNS tumors in Armenia. (3rd June 2022) - Hoveyan, Julieta; Grigoryan, Henrik; Hovsepyan, Shushan; Avagyan, Anna; Asatryan, Eduard; Tamamyan, Gevorg; Papyan, Ruzanna; Sargsyan, Lilit; Hakobyan, Lusine; Bardakhchyan, Samvel
Abstract: BACKGROUND: CNS tumors are the most common solid tumors in children and the leading cause of cancer related deaths. The incidence of CNS tumors is 1.7-6.21 cases per 100000 children. The aim of current study is to analyze epidemiological data, treatment and outcomes of children and young adults (<25 years) with CNS tumors in Armenia during last 25 years. METHODS: We have collected data of pediatric and young adult patients treated in neurosurgery department, three major chemotherapy clinics and radiation therapy department from 01.01.1995 to 31.12.2020 in Armenia. Incidence by gender, age at diagnosis, the time from first complaints to diagnosis, histopathology results and overall survival rates were calculated. RESULTS: The population-based data revealed 176 patients diagnosed with primary CNS tumors during 25 years. Among them 98 (55.7%) were males. Mean age at diagnosis was 7.07 years and the mean time from the first complaints to diagnosis was 6.55 months. Medulloblastomas and other embryonal tumors (26.7%), low grade gliomas (16.5%), retinoblastomas (12.5%) and high grade gliomas (10.8%) were the most common diagnosed malignancies. Craniopharyngiomas, germ cell tumors and other malignancies were observed in 9.1% of patients. For 24.4% histopathological data was missing. Surgery, chemotherapy and radiation therapy were performed in Armenia for 62.5%, 33.5% and 19.3% patients respectively. Follow up information was available for 119 (67.6%) patients. 5-year overall survival was 76%. CONCLUSION: Embryonal tumors and gliomas were the most common diagnosed CNS malignancies in Armenia which is consistent with international data. Multimodal treatment was often not available in Armenia during study period, especially for early cases. We hope recent advances in surgery, chemotherapy, and radiotherapy will help to improve treatment outcomes.